Tail-to-tail orientation of the Atlantic salmon alpha- and beta-globin genes. - Wagner, A.; Deryckere, F.; McMorrow, T.; Gannon, F. (HAL CCSD, 1994)
We report the cloning of a cDNA and two corresponding beta-globin genes of the Atlantic salmon (Salmo salar L.) as well as two genes for alpha-globins. Nucleotide sequence analysis of the cDNA shows that the predicted beta-globin peptide comprises 148 amino acids with a calculated molecular mass of 16,127 Da and an overall amino acid similarity of 40-50% to higher vertebrates and 60-90% to fish sequences. The study of the genomic organization of alpha- and beta-globin genes shows that, as is the case in Xenopus, the salmon genes are adjacent. Two sets of linked alpha- and beta-globin genes were isolated and restriction-enzyme polymorphisms indicate that they belong to two distinct loci, possibly as a result of the salmon tetraploidy. In each locus the alpha- and beta-globin genes are oriented 3' to 3' relative to each other with the RNA coding sequences located on opposite DNA strands. This is the first evidence for this type of arrangement found for globin genes. Moreover, while the linkage found in salmon and Xenopus supports the hypothesis of an initial tandem duplication of a globin ancestor gene, our results raise the question of the actual original orientation of the duplicated genes.